2006
DOI: 10.4161/cc.5.23.3535
|View full text |Cite
|
Sign up to set email alerts
|

EGF Induces Cell Motility and Multi-Drug Resistance Gene Expression in Breast Cancer Cells

Abstract: The epidermal growth factor receptor (EGFR) is important for normal development, differentiation, and cell proliferation. Deregulation of EGFR has been observed in breast cancer. EGFR and signal pathways activated by these receptors have been associated with an advanced tumor stage and a poor clinical prognosis in breast cancer; however, the precise mechanisms responsible for this process are still not known. Here we show that treatment of MCF-7 breast cancer cells with EGF activated Akt and ERK, induced morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 35 publications
2
50
0
3
Order By: Relevance
“…EGF over-expression could increase cell differentiation and proliferation, inhibit apoptosis and enhance invasiveness of cancer cells in many tumor types, including breast cancer [10][11][12][13]. The EGF gene contains an atypical TATA box, polypurine-rich motifs and consensus binding sequences for many transcription factors, e.g., NF-kB, GAS, AP-1, Sp1, C/EBP, etc.…”
Section: Introductionmentioning
confidence: 99%
“…EGF over-expression could increase cell differentiation and proliferation, inhibit apoptosis and enhance invasiveness of cancer cells in many tumor types, including breast cancer [10][11][12][13]. The EGF gene contains an atypical TATA box, polypurine-rich motifs and consensus binding sequences for many transcription factors, e.g., NF-kB, GAS, AP-1, Sp1, C/EBP, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[276][277][278] Recently, we and others have shown that aberrant activity of the PI3K/PTEN/Akt/mTOR signaling cascade can augment drug resistance in advanced CaP cells. 279,280 These reports detail several potential mechanisms responsible for increased chemoresistance including PI3K-induced overexpression of the MRP-1 drug pump as well as activation of the mTOR molecule that is downstream of PI3K/Akt.…”
Section: Treatment Of Prostate Cancermentioning
confidence: 99%
“…40 Our data showed that VCR increased the expressions of P-gp and MRP1 in HepG2 cells, and these upregulations were impaired by pCSH1-shNR. It was because that the expression levels of P-gp and MRP1 were regulated by ERKs and Akt, which were inhibited by pCSH1-shNR, 40,41 and the promoter of human MDR1 gene was shown to be a target for Ras. 42,43 Moreover, Ras-mediated activation of the MEK/MAP kinase pathway increases cellular levels of cyclin D1, but other effector pathways may also be important in cyclin D1 induction.…”
Section: Discussionmentioning
confidence: 99%